2004
DOI: 10.1007/s00125-004-1547-8
|View full text |Cite
|
Sign up to set email alerts
|

Metformin or gliclazide, rather than glibenclamide, attenuate progression of carotid intima-media thickness in subjects with type 2 diabetes

Abstract: Aim/hypothesis. Metformin is a well-known oral hypoglycaemic agent and has been commonly used, in combination with sulphonylurea, to treat type 2 diabetes. However, the advantageous effect of metformin plus sulphonylurea on diabetic macroangiopathy has yet to be clarified. To evaluate whether sulphonylurea or sulphonylurea plus metformin prevent diabetic macroangiopathy, we examined the progression of carotid artery intima-media thickness (IMT) as a surrogate end point. Methods. Subjects with type 2 diabetes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
3
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(58 citation statements)
references
References 30 publications
3
45
3
7
Order By: Relevance
“…The number of patients treated was based on the assumption of a change of 0.022 mm in the non-pioglitazone group, whereas the actual differences were 0.031 and 0.043 mm. This significant decrease even in the non-pioglitazone group possibly reflects the more frequent use of biguanides and -glucosidase inhibitors in the non-pioglitazone group 24,25) . Interestingly, the findings of this substudy mirror the results of the "parent" PROBE trial, which also found a non-significant trend towards improved macrovascular outcomes in the pioglitazone group versus the control group 15) .…”
Section: Discussionmentioning
confidence: 94%
“…The number of patients treated was based on the assumption of a change of 0.022 mm in the non-pioglitazone group, whereas the actual differences were 0.031 and 0.043 mm. This significant decrease even in the non-pioglitazone group possibly reflects the more frequent use of biguanides and -glucosidase inhibitors in the non-pioglitazone group 24,25) . Interestingly, the findings of this substudy mirror the results of the "parent" PROBE trial, which also found a non-significant trend towards improved macrovascular outcomes in the pioglitazone group versus the control group 15) .…”
Section: Discussionmentioning
confidence: 94%
“…A possible explanation for this discrepancy may be the fact that not all patients who lose weight experience reductions in their plasma renin and aldosterone levels (28,29). However, metformin is known to positively affect other parameters which influence the development of cardiovascular disease, regardless of any effect on BP (30,31). Our results agree with the literature regarding the effect of metformin on BMI reduction (9,12,13), reduction of daily insulin dose (9,12,13), biguanide-related sideeffects (21,24), and reduction of WC, which is a cornerstone for the diagnosis of metabolic syndrome and may play the role of a co-variate when other parameters are analyzed (18,32).…”
Section: Other Parametersmentioning
confidence: 99%
“…A PDX-1-expressziót gén-és fehérjeszinten egyaránt serkentette [29]. Endotheldiszfunkciót mérséklő, egyes gyulladásos tényezők képződését gátló, valamint a kísérletes körülmények kö-zött észlelt, érfali lipidlerakódást mérséklő hatásával magyarázzák az atherogenesist más SU-származékokéhoz képest lassító természetét [7]. Experimentális vizsgálat-ban igazolták nitrogén-monoxid-dependens vasodilatatiót serkentő [32,33], sőt streptozotocinnal kiváltott diabetesben, vérnyomást csökkentő tulajdonságát is [33].…”
Section: A Su-k Nem Receptoriális Tulajdonságaiunclassified
“…Az adatok értékelését nehezíti azonban, hogy az ismeretek nagy része experimentális megfi gyelésekből származik, továbbá, hogy pros pektív tanulmányokból származó "kemény végpontú" eredmé-nyek, illetve az egyes származékokat összehasonlító ("head-to-head") vizsgálatok nem, illetve csak korláto-zottan állnak rendelkezésre. Kétségtelen ugyanakkor, hogy egyre bővül a SU-hatás biokémiai hátterével kapcsolatos ismeretek köre [4,5,6], s nő a pancreasszelektívnek tartott származékok (a második generációs vegyü-letek közül a gliclazid) klinikai előnyeiről beszámoló közlemények [7,8,9,10] száma is.…”
unclassified